PSMA-PET/CT in Patients with Recurrent Clear Cell Renal Cell Carcinoma: Histopathological Correlations of Imaging Findings - Gühne, Falk (Diagnostics (Basel), 2021)
PET/CT with prostate-specific membrane antigen (PSMA)-targeted tracers has been used in the diagnosis and staging of patients with clear cell renal cell carcinoma (ccRCC). For ccRCC primary tumors, PET parameters were shown to predict histologic grade and features. The aim of this study was to correlate PSMA PET/CT with histopathological findings in patients with metastatic recurrence of ccRCC. Patients with ccRCC who underwent PSMA-targeted PET/CT and subsequent histopathological evaluation of suspicious lesions were included. Specimens underwent immunohistochemical marking. Lesion diameter, volume and tracer uptake were correlated with the extent and intensity of molecular PSMA expression and with clinical findings. Twelve PET-positive lesions of nine patients were evaluated. Eleven ccRCC metastases and one prostate carcinoma were detected histopathologically. Molecular PSMA expression was detected in all lesions, which intensity and distribution did not correlate with PET parameters. PSMA-targeted PET/CT is a feasible tool for the evaluation of patients with ccRCC but cannot reliably predict histologic features of metastases. PSMA may also be expressed in malignant lesions other than ccRCC, leading to incidental detection of these tumors.